2020
DOI: 10.1002/adfm.202000534
|View full text |Cite
|
Sign up to set email alerts
|

Porous Pd‐PdO Nanotubes for Methanol Electrooxidation

Abstract: Palladium (Pd) nanostructures are highly active non-platinum anodic electrocatalysts in alkaline direct methanol fuel cells (ADMFCs) and their electrocatalytic performance relies highly on their morphology and composition. Herein, a facile high-temperature pyrolysis method to synthesize high-quality Pd-palladium oxide (PdO) porous nanotubes (PNTs) by using Pd(II)-dimethylglyoxime complex (Pd(II)-DMG) nanorods as a selftemplate is reported. The chemical component of pyrolysis products highly correlates with pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 170 publications
(101 citation statements)
references
References 67 publications
2
99
0
Order By: Relevance
“…It is also likely that surface oxides such as PdO catalyze the reaction. This species promotes the catalytic activity of Pd nanocatalysts for the oxidation of organic molecules, as concluded from the findings by Sawangphruk et al, [53] Chen et al, [54] and Manzo-Robledo et al [55] It has been suggested that Pd-oxides limit the poisoning effect of adsorbed carbonaceous species by forming OH À species. As concluded from XPS analysis, Pd-CeO 2-NR /C forms more PdO species than Pd/C, positively affecting its catalytic behavior.…”
Section: Evaluation Of Catalytic Activity For the Orrmentioning
confidence: 79%
“…It is also likely that surface oxides such as PdO catalyze the reaction. This species promotes the catalytic activity of Pd nanocatalysts for the oxidation of organic molecules, as concluded from the findings by Sawangphruk et al, [53] Chen et al, [54] and Manzo-Robledo et al [55] It has been suggested that Pd-oxides limit the poisoning effect of adsorbed carbonaceous species by forming OH À species. As concluded from XPS analysis, Pd-CeO 2-NR /C forms more PdO species than Pd/C, positively affecting its catalytic behavior.…”
Section: Evaluation Of Catalytic Activity For the Orrmentioning
confidence: 79%
“…[71] To date, a variety of heterogeneous interfaces have been created for boosting electrocatalytic reactions, such as metal-metal, metal-metal oxide, and metal-metal sulfide interfaces. [72,73] Regarding the metal-metal interface, core-shell-type nanomaterials have been acknowledged as promising catalysts for electrochemical reactions. The lattice mismatch between the inner core and outer shell could induce lattice strain on the surface of nanomaterials.…”
Section: Interface Engineeringmentioning
confidence: 99%
“…[ 71 ] To date, a variety of heterogeneous interfaces have been created for boosting electrocatalytic reactions, such as metal–metal, metal–metal oxide, and metal–metal sulfide interfaces. [ 72,73 ]…”
Section: Advanced Regulation Of Ldmns For Enhanced Eelectrocatalysismentioning
confidence: 99%
See 2 more Smart Citations